Regulatory Capacity Review of Rwanda - International Finance Corporation; Multilateral Investment Guarantee Agency; World Bank (Washington, DC, 2017)
Regulatory reform has emerged as an important policy area in developing countries. For reforms to be beneficial, regulatory regimes need to be transparent, coherent, and comprehensive. They must establish appropriate institutional frameworks and liberalized business regulations; enforce competition policy and law; and open external and internal markets to trade and investment. This report analyses the institutional set-up and use of regulatory policy instruments in Rwanda. It is one of five reports prepared on countries in East and Southern Africa (the others are on Kenya, Uganda, Tanzania and Zambia), and represents an attempt to apply assessment tools and the framework developed by the Organization for Economic Cooperation and Development (OECD) in its work on regulatory capacity and performance to developing countries.